Stochastic processes in the structure and functioning of soil biodiversity - Lindo, Zoë; Bolger, Thomas; Caruso, Tancredi (Frontiers in Ecology and Evolution, 2023)
Ecologists are increasingly recognizing the importance of stochastic processes in generating spatial and temporal variation in biological communities. This variation is very high in soil, which hosts not <¼ of all biodiversity on Earth and is central to how terrestrial ecosystems respond to perturbations. Measurement errors, demographic stochasticity (individual variability in traits such as birth and death rates), and environmental stochasticity (fluctuations in environmental properties) are the three main sources of stochasticity in ecology. Here, we synthesize how these three sources of stochasticity are quantified and incorporated in the study of soil biodiversity, highlighting current limits, possible solutions, and future research needs. We stress the relevance of all these factors to our future understanding of terrestrial ecosystems via plant-soil and soil-climate interactions and feedbacks. In soil, measurement errors are due to the small size, high abundance, and broad distributions of soil organisms, which limit sampling in space and especially over time. We argue that positive autocorrelation is a main characteristic of soil environmental properties, which may have important consequences on the response of soil biota to perturbations. At a local scale, large populations of soil organisms also imply a minor role of demographic stochasticity. Despite demographic stochasticity being a less significant source of variability than environmental stochasticity, we show that demographic stochasticity can be sizeable, but that within soil systems, stochasticity of environmental conditions must be accounted for. Explicit consideration of stochastic processes in soil biodiversity research is essential to our future understanding of the processes that control soil biodiversity. In classical ecology, stochasticity implies probabilistic predictions in terms of population growth, extinction, species coexistence, and community diversity. In soil, stochasticity implies very variable responses to climate change and the soil-climate feedback. Future studies will have to identify the major sources of environmental stochasticity with a particular focus on the interaction between multiple global change factors.